ON THE NATURAL LINK FROM ISLAM TO INFORMATION TECHNOLOGY - Ozkan, Necmettin (Journal of Information Systems and Digital Technologies, 2020)
While the use of information technology (IT) in the Islamic context is known, the use of Islam in or for IT is new. This study advocates that Islam should be involved in the production phase, long before the use, of IT. The study, with the aim of defining and introducing the subject within a general frame and specific examples, elaborates the subject with the human, process and technology dimensions. The study promotes the possibility of establishing a connection from Islam to IT for the following two (or more) reasons: 1) everything about human beings who are the common concern of Islam and IT is the focus of Islam. 2) The human beings, the caliph of the Creator, Who has created the universe in the best way, are bound to create IT by inspiring Him. Considered the perfect creation is already available, IT and human organizations will not be better or different from this perfection. In this manner, there is a lot to guide and teach to the new invention of mankind, by the Creator and religious Islam, which leaves no single untouched place in the universe so far and at the future.